2020
DOI: 10.1371/journal.pone.0234464
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of the optimal numbers of examined and positive lymph nodes to the 8th edition of American Joint Committee on Cancer (AJCC) staging for 758 patients with distal cholangiocarcinoma

Abstract: Introduction The American Joint Committee on Cancer (AJCC) recommended retrieval of at least 12 lymph nodes and firstly classified N category by the number of positive lymph nodes (PLNs) for Distal Cholangiocarcinoma (DCC). Objective The end of this cohort study was to explore the optimal cutoff values of the number of examined lymph nodes (ELNs) and PLNs to better stratify patients by utilizing a population-based database. Methods A number of 758 patients with DCC from the Surveillance, Epidemiology, and End … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Whether age is an independent risk factor for DCC remains controversial. You et al ( 19 ) reported that age was significantly related to the prognosis of DCC, but Chen et al ( 30 ), Wu et al ( 31 ), and the results of this study reached the opposite conclusion. This may be due to the limitations of the different studies.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Whether age is an independent risk factor for DCC remains controversial. You et al ( 19 ) reported that age was significantly related to the prognosis of DCC, but Chen et al ( 30 ), Wu et al ( 31 ), and the results of this study reached the opposite conclusion. This may be due to the limitations of the different studies.…”
Section: Discussioncontrasting
confidence: 83%
“…Multivariate analysis also indicated that in addition to LODDS stage, tumor grade, SEER historic stage, and tumor size were also independent risk factors for DCC patients. The prognostic value of these factors has been verified in a variety of tumors, including DCCs (4,(29)(30)(31). Whether age is an independent risk factor for DCC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion from Park et al that although DOI is useful to separate T1-3, the measurement of DOI does not need to be rigorously and stringently performed ( 31 ). Wu et al in a study of 758 patients with dCCA to examine the optimal numbers of positive lymph nodes revealed that N1 with 1–2 node-positive (1–3 for 8th AJCC) and N2 ≥ 3 nodes positive (≥4 for 8th AJCC) can significantly separate survival time of N1 and N2 better than 8th AJCC staging system ( 29 ). Other studies propose additional factors, such as a prognostic factor, to improve prognosis in dCCA.…”
Section: Discussionmentioning
confidence: 99%
“…The 7th edition showed low-performance separation of T1 vs. T2 and T2 vs. T3, and no significant difference in the 5-year survival rate, whereas the 8th edition provided a significant difference in separation of T1 vs. T2 and T2 vs. T3, leading to better prognostic predictability ( 28 ). As far as inclusion of DOI and number of lymph node metastasis is concerned, the verdict is still out ( 29 32 ). There has, however, been increasing studies proposing revisions of the updated 8th edition and alternative staging systems for classification ( 33 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node invasion is a prognostic for overall survival in all malignancies that display lymphatic spread, however there is not a consensus regarding the number of lymph nodes that defines an adequate dissection in patients with dCCA ( Table 4 ). The AJCC has endorsed the retrieval of at least 12 nodes for adequate lymph node staging [ 57 , 58 , 73 , 74 , 75 ]. Due to the influential impact of lymph node metastasis on treatment outcome, a study by Yoshida et al recommended CW or PPW with extended lymphadenectomy, including periaortic lymph node dissection that extended from the celiac axis superiorly, to the inferior mesenteric artery inferiorly, the lateral margin of the inferior vena cava, and the medial margin of the abdominal aorta for optimal curative resection of dCCA.…”
Section: Surgical Principlesmentioning
confidence: 99%